Проблеми розвитку малого бізнесу в Україні - Максименко, Наталія Дмитрівна (НТУ "ХПІ", 2013)
In the article the basic problems of activity of small forms of menage are considered in Ukraine. The special attention is spared the exposure of factors of negative influence on development of activity of small business and basic tasks development of small enterprise are considered taking into account his role in functioning of economy.
Keywords: ринок; підприємництво; економіка; система господарська; товари; послуги